More Than Effects in Skin: Ultraviolet Radiation-Induced Changes in Immune Cells in Human Blood - Hart, Prue H.; Norval, Mary (Frontiers in Immunology, 2021)
Cells of the skin and circulation are in constant two-way communication. Following exposure of humans to sunlight or to phototherapy, there are alterations in the number, phenotype and function of circulating blood cells. In this review, only data obtained from human studies are considered, with changes induced by UV radiation (UVR) exposure described for phagocytic leukocytes and peripheral blood mononuclear cells plus their component T and B cells, natural killer cells and dendritic cells. These immune modulations illustrate the potential of UVR to have therapeutic effects beyond the skin, and that sunlight exposure is an important environmental influence on human health.